Olive industry solid waste-based biosorbent: synthesis and application in wastewater purification - CAN, ZEHRA SEMRA; HACIOSMANOĞLU, GÜL GÜLENAY (My University, 2023)
In this work, we present a process for converting olive industry solid waste (OISW) into a value-added material with ionic receptors for use in the removal of toxic metal ions from wastewater. This 3D polymer is a promising adsorbent for large-scale application, since it is a low-cost material made from agricultural waste and showed exceptional performance. The synthesis of the network polymer involved the carboxymethylation of OISW and curing of the carboxymethylated OISW at an elevated temperature to promote the formation of ester linkages between OISW’s components. FT-IR, atomic force microscopy, and thermal analysis were performed on the crosslinked product. The adsorption efficiency of the crosslinked carboxymethylated OISW toward Pb(II), Cu(II), and other toxic metal ions present in sewage was evaluated as a function of adsorbent dose, temperature, pH, time, and initial metal ion. The percentage removal of about 20 metal ions present in a sewage sample collected from a sewer plant located in the Palestinian Territories was determined. The adsorption efficiency did not drop even after six cycles of use. The kinetic study showed that the adsorption process follows the Langmuir isotherm model and the second-order adsorption rate. The experimental Qe values of 13.91 and 13.71 mg/g were obtained for Pb(II) and Cu(II) removal, respectively. The thermodynamic results confirm the spontaneous metal bonding to the receptor sites of the crosslinked carboxymethylated OISW.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); 3D polymer; cellulose; hemicellulose; lignin; Langmuir isotherm; wastewater; adsorption; kinetic